Effect of modified pomace on copper migration via riverbank soil in southwest China - Chen, Lingyuan; Abbas, Touqeer; Yang, Lin; Xu, Yao; Deng, Hongyan; Hou, Lei; Li, Wenbin (PeerJ, 2021)
To explore the effects of modified pomace on copper migration via the soil on the banks of the rivers in northern Sichuan and Chongqing, fruit pomace (P) and ethylene diamine tetra-acetic acid (EDTA) modified P (EP) were evenly added (1% mass ratio) to the soil samples of Guanyuan, Nanbu, Jialing, and Hechuan from the Jialing River; Mianyang and Suining from the Fu River; and Guangan and Dazhou from the Qu River. The geochemical characteristics and migration rules of copper in different amended soils were simulated by column experiment. Results showed that the permeation time of copper in each soil column was categorized as EP-amended > P-amended > original soil, and the permeation time of amended soil samples at different locations was Jialing > Suining > Mianyang > Guangan > Dazhou > Nanbu > Guanyuan > Hechuan. Meanwhile, the average flow rate of copper in each soil column showed a reverse trend with the permeation time. Copper in exchangeable, carbonate, and iron–manganese oxide forms decreased with the increase of vertical depth in the soil column, among which the most evident decreases appeared in the carbonate-bonding form. The copper accumulation in different locations presented a trend of Jialing > Suining > Mianyang > Guangan > Dazhou > Nanbu > Guangyuan > Hechuan, and the copper content under the same soil showed EP-amended > P-amended > original soil. The copper proportion of the carbonate form was the highest in each soil sample, followed by the exchangeable form. The proportions of iron-manganese oxide and organic matter forms were relatively small. A significant correlation was observed between the cation exchange capacity and the copper content in exchangeable and carbonate forms. Moreover, total organic carbon and copper contents were negatively correlated.
Keywords: Copper; Modified pomace; Riverbank soil; Geochemical characteristics; Column experiment